What Is (Fake) News? Analyzing News Values (and More) in Fake Stories - Tandoc Jr., Edson C. (2021)
‘Fake news’ has been a topic of controversy during and following the 2016 U.S. presidential election. Much of the scholarship on it to date has focused on the ‘fakeness’ of fake news, illuminating the kinds of deception involved and the motivations of those who deceive. This study looks at the ‘newsness’ of fake news by examining the extent to which it imitates the characteristics and conventions of traditional journalism. Through a content analysis of 886 fake news articles, we find that in terms of news values, topic, and formats, articles published by fake news sites look very much like traditional—and real—news. Most of their articles included the news values of timeliness, negativity, and prominence; were about government and politics; and were written in an inverted pyramid format. However, one point of departure is in terms of objectivity, operationalized as the absence of the author’s personal opinion. The analysis found that the majority of articles analyzed included the opinion of their author or authors.